The outcomes of root canal treatment undertaken by dental students in Kulliyyah of dentistry, IIUM: Periapical health - Mat Daud, Muhamad Sharifuddin; Mohd Ibrahim, Mohamad Shafiq; Mustaffa, Musliana (2021)
The aim of this study is to determine the outcome of root canal treatment based on periapical healing. Two calibrated researchers assessed the clinical and radiographic presentations of 175 root canal treated teeth with at least 6 months recall period. Periapical status was determined with Periapical Index score and compared with the preoperative score. Univariate logistic regression was used to assess the association between prognostic factors (preoperative, intraoperative, and postoperative) with strict criteria and loose criteria. The success rate was 60% when using strict criteria and 99% when using loose criteria. Preoperative periapical status influenced the success where the cases with PAI score 1 and 2 significantly has higher success rate when compared with the cases with PAI ≥3.